Hubungan Aktivitas Fisik dengan Ketahanan Kardiorespirasi pada Mahasiswa Program Studi Kedokteran Universitas Mulawarman - Qhuzairi, Muhammad Rezwan; Magdaleni, Agustina Rahayu; Sulistiawati, Sulistiawati; Sawitri, Endang; Putra, Indra Sukmana (Jurnal Kesehatan Andalas, 2023)
Cardiorespiratory endurance is the ability of the body's circulatory and respiratory system to meet the oxygen needs of the muscles as a source of energy production during sustained physical activity. One of the factors that influenced the level of cardiorespiratory endurance of a person was physical activity. Objective: To determined the relationship between physical activity and cardiorespiratory endurance. Methods: It was an analytic observational with a cross-sectional study. Data were taken from primary data that were measured directly on 97 students of the Medical Study Program at Mulawarman University who were selected using a purposive sampling technique. The data collected included physical activity using the Global Physical Activity Questionnaire (GPAQ) and cardiorespiratory endurance using Queen's College Step Test. The statistical analysis used was Spearman's correlation test with a significance value of p <0.05. Results: The statistical test showed that the relationship between physical activity and cardiorespiratory endurance was p = 0.003 and r = 0.295. Conclusion: There was a significant positive relationship between physical activity and cardiorespiratory endurance, and the relationship's strength was weak.Keywords: Â cardiorespiratory endurance, global physical activity questionnaire, physical activity, queenâ€™s college step test